The Caluation of Microsoft Coproration - Lee, Ka Lou (University of Saint Joseph, 2021)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Study of the Valuation of ManpowerGroup Inc - Lei, Choi Ieng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Under Armour - Leong, Ka Wa (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Marriott International, Inc - Ian, Kin Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The Financial Valuation of Waste Management, Inc: Daniela Wai Ka, Leong - Leong, Wai Ka (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Alibaba Group Holding Limited - Chan, Man Hong (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Netflix, Inc - Tong, Si Weng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A financial Valuation Study for Moody’s Corporation - Sio, Lai Teng (University of Saint Joseph, 2023)
This study presents the intrinsic value of Moody’s Corporation, a leading credit rating agency in the U.S. The results of the valuation were compared to the market value of Moody’s Corporation of the same date. The aim of the research is to provide a perspective to the investors on whether the actual value of the Company was overvalued or undervalued in the market, and how much the volatility of the stock price by the change of some factors. Both qualitative and quantitative analyses were applied in the research. The historical data, economic outlook, and the Company’s strategies were collected to be the metrics to determine the intrinsic value and provide an analysis of the prospects of Moody’s Corporation. Three valuation models were applied in the research to estimate the intrinsic value of the Company’s common stock. The cost of debt, cost of equity, the weighted average cost of capital, and the market risk premium were introduced and calculated in the research as they were the critical components in the valuation process. Since the valuation was based on assumptions and historical data to determine future growth, which indicates that the results could be changed due to uncertain factors. This study demonstrates that there was some discrepancy between the stock’s market price and the intrinsic value per share of Moody’s Corporation as of December 31, 2021
Keywords: Intrinsic Value; Moody's; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph; Valuation

The VALUATION OF TENCENT HOLDINGS LIMITED - Lo, Hao Weng (University of Saint Joseph, 2023)
This study analyzed Tencent Holdings Limited’s internal and external factors and future strategies, forecasted the financial statements of the Company for the next ten years, and measured the intrinsic value of the Company on December 31, 2021 and compared it with the stock market price on the same date. The share price’s sensitivity analysis was also conducted to understand the Company's capital structure and profitability, and the sensitivity analysis can be used to reflect the impact of these factors and strategies on the future share price, which can have a high impact on investors' future investment decisions. This study also used the SWOT Analysis and Michael Porter's Five Forces Analysis to analyze the Company's strengths, weaknesses, opportunities and threats and the Five Competitive Forces that shape the technology industry to evaluate the Company's external and internal environment and enrich the management with a more intuitive analysis leading to recommendations
Keywords: PEST Analysis; SWOT Analysis; Technology Industry; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A Financial Valuation of Realty Income Corporation - Rodrigues, Ricardo David Almeida Fernandes (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A FINANCIAL VALUATION OF ORACLE CORPORATION - Maung, Ye Thu Anug (University of Saint Joseph, 2023)
Oracle Corporation (hereinafter referred to as Oracle, ORCL, or ‘the Company’) is an American multinational company that provides solutions of products and services that serve the enterprises’ information technology (IT) environment. This thesis is to conduct a business analysis of the Company from a financial perspective, determining the Company’s intrinsic value as of May 31, 2021, and comparing it with the respective market value. Thus, this thesis will study, evaluate, and present an overview of the Company, an analysis of the Company’s market, industry, strategy, financial performance, including external and internal factors, a ten-year pro forma financial statement forecast, and the techniques of using the three discounted cash flow models to estimate the intrinsic value of Oracle. The obtained results from the three valuation models, including the Enterprise Discounted Cash Flow (EDCF) model, the Adjusted Present Value (APV) model, and the Discounted Economic Profit (DEP) model, show that the Company’s intrinsic values were estimated at $74.57, $75.21, and $74.82, respectively. When the results were used to compare with the market price of Oracle’s shares as of May 31, 2021, at $78.74, it reflects that the Company was overvalued
Keywords: Analysis; Financial Valuation; Oracle Corporation; Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph